Advanced scenarios in Azure Functions - Malik, Sahil (Apress, 2019)
In this video on Azure Functions, you will learn about the most relevant advanced features of Azure Functions. The video is broken down into concise yet complete segments so that you can discover how to write, debug, and diagnose Azure Functions on a need-to-know basis. As various cloud offerings move towards serverless computing, Azure Functions has emerged as Microsoft Azure's serverless computing platform. This video goes a step beyond coding in the browser and introduces you to a typical view of Azure Functions, including writing in VS Code, debugging, and diagnosing issues. What You Will Learn. Orchestrate Azure Functions. Diagnose using Kudu. Debug Azure Functions. Write Azure Functions in VS Code. Who This Video Is For: NodeJS or C# developers who are interested in learning about Azure Functions. It is a 200 level video.